Review Artikel : Analisis Kandungan Fluoride dalam Pasta Gigi dengan Metode Potensiometri dan Elektroda Selektif Ion - Syuhriah Syuhriah; Laelatun Nupus; Fadiya Qotrunnada; Firdha Senja Maelaningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Toothpaste is an essential product for maintaining dental health, where fluoride is one of the key components commonly added. Fluoride plays a crucial role in strengthening enamel and preventing cavities, but the fluoride content in toothpaste must be adjusted according to age groups to avoid the risk of fluorosis, especially in children The literature review aims to evaluate the fluoride content in toothpaste analyzed using potentiometric methods with fluoride ion-selective electrodes (F-ISE). Through a literature review of five research articles published from 2014 to 2024, significant variations in fluoride levels were found. Some products met WHO standards (1000–1500 ppm), while others did not meet criteria, having either too low or too high fluoride content. The potentiometric method proved to be accurate and reliable; however, stricter supervision and regulations are needed to ensure product safety. In conclusion, it is important for consumers to understand the fluoride levels in the toothpaste they use and to ensure the selection of safe and effective products.